Peran Budaya Organisasi Dalam Meningkatkan Kinerja Karyawan - Ridwan Ridwan (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
The research objective is to explain the role of organizational culture in improving employee performance in an organization. The research was conducted qualitatively with a library study approach. Data collection techniques with documentation studies. Data processing with reduction, data presentation and conclusion. The results showed: (1) organizational culture is a habit that arises as a result of the formation and implementation of values, norms and policies by leaders in the organization. (2). Employee performance is the result of work shown by employees while completing their duties in the organization. (3) the role of organizational culture in improving employee performance, namely: employees need to pay attention to innovation in risk taking, attention to detail, benefit orientation, people orientation, team orientation, aggressiveness, and work stability in order to form good performance. This will be useful in building employee habits to work according to standards set by the organization. Therefore, a leader needs to initiate some ideas or decisions regarding values, norms, and policies that are able to bind and lead employees towards familiarizing themselves with these ideas to form a work culture for the organization.